ANALISIS EKRANISASI NOVEL KE FILM SURAT KECIL UNTUK TUHAN - Nurul Aini; Maisaratun Najmi; Yatno Karyadi (Cinelook: Journal of Film, Television, and New Media, 2023)
This study discusses the process of ecranizing the novel into a film form Surat Kecil Untuk Tuhan directed by Harris Nizam. The purpose of this study is to describe the changes and find out the motives for the differences between the novel and the film after the ecranization process takes place based on the aspects of additions, subtractions, and deletions. The method used in this study is a qualitative method which is presented descriptively using George Bluestone's ecranization theory approach to present data accompanied by a description of the research results.The results of identifying the story elements of novels and films are used as comparative data on the changes that occur from the ecranization of novels to films. Each element of the story is related to one another. Changes in one element of the story from the ecranization of the novel to the film cause changes in other story elements. Based on the research that has been done, it is concluded that the ecranization of the novel Surat Kecil Untuk Tuhan has undergone several changes, including shrinking, adding and varying changes. These changes occur in the elements of the theme, story characters, setting, and plot. The most significant change is the shrinking of the plot, this occurs because the ecranization film is actually a summary of the story from the novel.